Materiales educativos, Concreto y Gráfico Representativo, y su influencia en la motivación para el aprendizaje significativo de. Lógico matemática en educandos de primaria - Meléndez Díaz, José Humberto (2001)
The present experimental investigation was carried out with the students he/she gives the second grade he/she gives primary education he/she gives the C.E. Nº 00536 belonging to the district and county gives Rioja, region San Martín. The problem, hypothesis and general objective have been designed in function to the variables: independent, educational material (I sum up and representative graph) and educandos (males and women); and clerk, motivation for the significant learning. The theoretical explanation gives the concrete educational material and give the material educational representative graph in its process he/she gives generation he/she gives motivation for the significant learning, it has been sustained in the theory he/she gives Piaget and Ausubel, respectively. Two hypothesis was formulated: the alternating hypothesis whose presumption was gives it a significant interaction, while the supposition gives the null hypothesis it was the nonexistence he/she gives interaction. Twenty educandos conformed the sample, the design factorial 2 x was used 2, the procedure consisted on the application he/she gives a test to evaluate the dependent variable Made the contrastación gives the hypothesis the results they evidenced a significant interaction. In consequence the summations configure their generality, specifying that so much the concrete educational material as the material educational graph representative interaccionan significantly generating motivation for the learning.